2013
DOI: 10.1253/circj.cj-12-1529
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Imaging of Carotid Plaque Neovascularization Is Useful for Identifying High-Risk Patients With Coronary Artery Disease

Abstract: A previous study indicated that plaque instability is not merely a local vascular occurrence, 11 but rather exists simultaneously at multiple sites in the systemic vascular bed. It is therefore possible that instability of coronary plaque could be assessed by evaluating plaque neovascularization in the carotid arteries. This study therefore examined whether CEUS of the carotid artery provided information on the severity and instability of coronary artery disease (CAD) and also assessed the efficacy of statin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…These findings highlight the role that detailed carotid ultrasonography can play in monitoring response to therapy. 23 Plaque imaging on ultrasonography has also been effectively used in selecting carotid revascularization candidates. Ballotta et al 6 used CEUS to select patients with symptomatic carotid plaques with < 50% stenosis.…”
Section: Ultrasound Plaque Imaging In Medical and Surgical Managementmentioning
confidence: 99%
“…These findings highlight the role that detailed carotid ultrasonography can play in monitoring response to therapy. 23 Plaque imaging on ultrasonography has also been effectively used in selecting carotid revascularization candidates. Ballotta et al 6 used CEUS to select patients with symptomatic carotid plaques with < 50% stenosis.…”
Section: Ultrasound Plaque Imaging In Medical and Surgical Managementmentioning
confidence: 99%
“…It is therefore possible that instability of coronary plaque could be assessed by evaluating plaque instability in the carotid arteries. Our previous study also demonstrated that a higher grade of the carotid plaque neovascularization assessed using CEUS was associated with more severe and unstable coronary artery disease (CAD) that was characterized by more complex and extensive coronary lesions [20]. A recent report showed that contrast enhancement of the carotid artery, assessed using CEUS, had the potential to predict coronary events in patients with CAD [21].…”
Section: Introductionmentioning
confidence: 97%
“…CEUS has recently been used to visualize intraplaque neovascularization as an element of vulnerability. 4,[8][9][10][11][12] The source of neovascularization is direct branching from the vasa vasorum or the intimal surface. These areas are very fragile, and plaque hemorrhage can easily occur.…”
Section: Resultsmentioning
confidence: 99%